2015
DOI: 10.1136/bjsports-2014-094306
|View full text |Cite
|
Sign up to set email alerts
|

Even a low-dose of moderate-to-vigorous physical activity reduces mortality by 22% in adults aged ≥60 years: a systematic review and meta-analysis

Abstract: A dose of MVPA below current recommendations reduced mortality by 22% in older adults. A further increase in physical activity dose improved these benefits in a linear fashion. Older adults should be encouraged to include even low doses of MVPA in their daily lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
287
1
11

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 459 publications
(334 citation statements)
references
References 80 publications
12
287
1
11
Order By: Relevance
“…Furthermore, shorter one-leg standing time showed a significant association with early pathological changes in the brain, such as asymptomatic cerebral small vessel disease, in the general population [24]. Decreased physical function, fracture injury, and stroke prevent patients with cardiovascular disease from participation in physical activity or regular exercise, and a sedentary lifestyle has already been established as a strong risk factor for poor prognosis in older adults [25] and cardiac patients [26, 27]. It may explain the mechanism underlying the association between shorter one-leg standing time and poor survival in older adults with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, shorter one-leg standing time showed a significant association with early pathological changes in the brain, such as asymptomatic cerebral small vessel disease, in the general population [24]. Decreased physical function, fracture injury, and stroke prevent patients with cardiovascular disease from participation in physical activity or regular exercise, and a sedentary lifestyle has already been established as a strong risk factor for poor prognosis in older adults [25] and cardiac patients [26, 27]. It may explain the mechanism underlying the association between shorter one-leg standing time and poor survival in older adults with cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivity is contributing to the burden of Australia's aging population on the health care system [11,12]. Interventions are needed to promote physical activity in older adults to help them to maintain their health and prevent chronic disease and mental health problems as they age [13].…”
Section: Introductionmentioning
confidence: 99%
“…This shows that almost all loss of PA is highly deleterious, and that moderate-intensity activity, even in small amounts, is beneficial. Even light-intensity PA can be important in preventing cancer [23], and this is possibly because increases in light-intensity PA are related to relative reductions in SB. A metaanalysis of relationships between SB and cancer suggested that SB was associated with overall cancer risk and with the risk of uterine cancer, colon cancer, breast cancer, and lung cancer, specifically [24].…”
Section: Effects Of Physical Activity On Cancer Preventionmentioning
confidence: 99%